Basal Cell Carcinoma (BCC) with Risk Factors of Exposure to Burns: A Case Report Study - Ningtyas, Indri Ari; Densy Violina H; Yohana Octavianda (HM Publisher, 2024)
Basal cell carcinoma (BCC) is the most common skin cancer, with a higher incidence than all other malignancies combined. Although metastases are rare, patients with multiple or frequently recurrent BCC can suffer from major and difficult-to-manage comorbidities. The choice of therapy in cases of skin cancer must be adjusted based on the type of histological lesion, size, location and age of the patient. No single therapy is ideal for all lesions. We report a case of BCC in a woman in a limited health facility without a dermatologist venereology oncology specialist. A 41-year-old woman came with complaints of a lump on her right cheek that had been slowly enlarging for the last 4 years and a week ago complained of itching at the edge of the lump. Local examination revealed a skin-colored nodule with surrounding telangiectasis. Even though the lump previously did not show any symptoms, the patient wanted the lump removed. The doctor decided to perform excision surgery. Histopathology results showed nodular BCC and the tumor had grown to the edge of the tissue, therefore the doctor decided to refer to an oncologist for additional surgery or radiotherapy. In conclusion, multiple BCC in women in limited health facilities is a complex challenge. Collaboration between general practitioners, specialist doctors, and other stakeholders is needed to increase access to quality health services and improve treatment outcomes for patients with BCC in remote areas.